The Effect Of Communicative Language Teaching On Speaking Fluency Of University Efl Students - Abdumajidov Xusan (Zien Journals, 2026)
This study investigates the impact of Communicative Language Teaching (CLT) on the speaking fluency of university EFL students. Developing speaking fluency is a persistent challenge for EFL learners, particularly in contexts with limited authentic communication opportunities. A quasi-experimental design was adopted, involving undergraduate EFL students who participated in communicative activities such as pair work, role-play, information-gap tasks, and group discussions over an eight-week period. Pre-test and post-test speaking assessments were conducted to evaluate changes in fluency, with data analyzed using both quantitative and qualitative methods. The results reveal a significant enhancement in students’ speaking performance, including increased speech rate, reduced hesitation, and higher confidence in oral communication. These findings demonstrate that CLT fosters an interactive and supportive learning environment conducive to fluency development. The study provides empirical evidence for the effectiveness of CLT in university EFL contexts and offers practical implications for language instructors aiming to improve students’ oral proficiency in English
Keywords: Communicative Language Teaching; speaking fluency